Integrating Maqāṣid Sharī‛ah into Emergency Response Management: An Islamic Safety Governance Framework - Mohammad Muslih; Rindang Diannita (Universitas Islam Sultan Agung, 2026)
Purpose - Modern emergency response management systems are largely shaped by technocratic approaches that prioritise procedural compliance and risk control. However, these approaches often insufficiently integrate ethical and value-based considerations as foundations for decision-making, thereby creating a gap between technical effectiveness and moral responsibility in protecting human life. This study develops the Islamic Emergency Response Framework (IERF) as a value-based safety governance model by integrating the principles and objectives of Islamic law (maqāṣid al-sharīʿah).Methodology/approach - This study adopted a qualitative conceptual approach based on systematic literature synthesis, bringing together maqāṣid al-sharīʿah theory, safety science, and risk governance. The analysis centered on the principle of protection of life (ḥifẓ al-nafs) as a normative foundation and translated it into operational mechanisms within contemporary emergency response systems. In doing so, the study established a systematic connection between Islamic normative principles and practical safety governance.Findings - The findings reveal that the IERF consists of four interrelated dimensions: normative values, ethical governance, safety management systems, and operational emergency response. The framework not only strengthens the technical capacity of safety systems but also reorients decision-making processes towards ethical responsibility and the protection of life (ḥifẓ al-nafs).Conclusion - The study concludes that integrating maqāṣid al-sharīʿah into emergency response management transforms it from a predominantly procedural system into a value-based governance framework. Its primary contribution lies in proposing a conceptual model that bridges the epistemological gap between Islamic legal theory and contemporary safety practices. The study also offers scholarly implications for developing more human-centred, accountable, and sustainable emergency response systems across diverse organisational contexts.